Pembelajaran Mufrodat pada Pelajar Tuli Menggunakan MMR dan Android di SLB B Karya Ibu Palembang - Ilham Solihin; Zulkipli Lessy (Journal on Education, 2023)
The success of a learning activity is supported by the ability of students to build curiosity through appropriate learning methods. Learning for children with special needs when receiving and conveying information, they use sign language as a means of receiving and conveying information. A fixed and precise method is needed for deaf children. The researcher chose MMR "Reflexive Magernal Method" and android as the media. These methods and media are applied at the Deaf SLB B Karya Ibu Palembang. By using the Mixed Methods approach, a combination of qualitative and quantitative methods together. The research model used is sequential exploratory, in the early stages using qualitative and quantitative methods. Data obtained from observation, interviews, and tests. Based on the results of research using the SPSS application with the T Test. There is a significant difference, namely 77.92 <85.48, it can be concluded that Ha is accepted, Ho is rejected, the difference is in the average value of the control and experiment. Output Group Statistics average value, namely the experimental class and the control class. It was concluded that there were differences in learning outcomes before and after using the MMR method in class XI students at Deaf SLB B Karya Ibu Palembang. While the effectiveness can be seen from the F test obtained 0.05 <0.216 meaning that Ho is rejected and Ha is accepted, significant effectiveness in the MMR method.